Onions in the stew - MacDonald, Betty Bard (Seattle University of Washington Press, 2016)
"In Onions in the Stew, MacDonald is in unbuttonedly frolicsome form as she describes how, with husband and daughters, she set to work making a life on a rough-and-tumble island in Puget Sound, a ferry-ride from Seattle. "Onions in the Stew" describes Betty MacDonald's years on beautiful Vashon Island in Puget Sound in happy times with her second husband and two daughters. During this time, fame as a writer finally knocked on her door. The book covers the period from 1942 to 1954. It opens just after Pearl Harbor with divorced mother Betty and her two daughters, 12-year-old Anne and 11-year-old Joan, living in her mother's home and Betty working in a building contractor's office. She meets and marries Donald MacDonald and they start searching for a home; unable to find a suitable one in Seattle or the mainland suburbs as a result of wartime influx of population, they try the local islands and finally find a property on Vashon Island. The early part describes the problems of commuting from a home without a road. Her daughters are at a painful state (they're boy crazy!), putting on lipstick to gather driftwood, switching from hair curlers to hair straighteners and coming up with mysterious ailments to avoid homework. Betty is sunk, miserable at having brought this apparent disaster on them all. Yet, in the midst of the humorous difficulties, the family finds a special value in the life they are creating--a value they wouldn't trade for anything in the world!"--Provided by publisher.
No money and no furniture -- Owner desperate -- Two million if by sea -- Life as usual in a very unusual setting -- God is the boss -- We made it ourselves -- The problem is to hold it back -- Cirripeds not wanted -- Other friends and enemies -- Master of none -- Bringing in the sheaves -- Triple that recipe -- Why don't you just relax, Betty? -- Advice, anybody? -- Adolescence, or please keep Imogene until she is thirty -- Onions in the stew.
Originally published: Philadelphia : J.B. Lippincott Company, 1955.
108113
Keywords: MacDonald, Betty Bard -- Homes and haunts -- Washington (State) -- Vashon Island; 1900-1999; Authors, American -- 20th century -- Biography; Country life -- Washington (State) -- Vashon Island; Families -- Washington (State) -- Vashon Island; Manners and customs; Vashon Island (Wash.) -- Social life and customs; Vashon Island (Wash.) -- Biography; 20th century; Autobiographies; Biographies